Retificador trifásico de fator de potência verdadeiramente unitário sem a utilização de filtros senoidais - Thiago Morais Parreiras (2015)
The scope of this work is to propose an alternative and simple solution to several applications where high power converters are used in interface with the grid in both cases, supplying or demanding power from it. In these cases is of great interest to obtain low current harmonic content due to the magnitude of the converted powe Reduced distortion is normally achieved through the application of switching frequencies as high as possible and the use of sinusoidal filters, however thisalternatives lead to reduced converter efficiency and increased cost of the solution. A trade-off between such factors must be found. In this context is proposed the True Unity Power Factor (TUPF) rectifier which aims to mitigate all current harmonics up to the fiftieth order though the combination of a selective harmonic elimination (SHE) strategy and a conventional three winding transformer with switching frequenciesaround 1kHz. The work develops through an extensive implementation analysis of SHE modulator and the commutation angles calculation needed to the desired harmonic elimination. Following it, this modulator, which was originally thought in steady-state, is analyzed in high dynamic applications, as is the case of the current control needed to active and reactive power control in active rectifiers. Finally, the TUPF rectifier is presented with its several possible topologies, which makes its usecost-effective for medium or low voltage applications with the necessity ofbidirectional power flow or not. All propositions stated are supported for simulations results and, in some cases, for experimental results